INVESTIGATING ENGLISH LANGUAGE EDUCATION STUDENTS’ READING PREFERENCES - Rahmawati Khadijah Maro; Rosalin Ismayoeng Gusdian; Berliana Febrianti Safitri (University of Kuningan, 2020)
This study aimed to determine students' preferences for their reading materials and dig out the benefits of their reading preferences. A descriptive research design was applied in this study. Two instruments were employed to obtain the data, namely a questionnaire and an interview guide. The subjects of this study were 35 third semester students of the English Language Education Department. These participants were selected by using a simple random sampling technique. In the data collection procedure, the participants filled in the questionnaire. Then, three of the participants were selected further to be interviewed. The data were then analyzed by calculating each item in the survey to obtain the final result in the form of a percentage, transcribing, and examining the interview result. The findings found that most of the students preferred novels as their reading material with 54,2%. Furthermore, as many as 31,4% preferred the genre of fiction. Several benefits from having their own preference in reading constitute (1) the students were able to comprehend the content of the reading material easily, (2) the students got more interested in reading, (3) the students gained broader knowledge, and (4) the students got attached to and focused on the text. Overall, this study implies that English language education students preferred novels as their reading material and fiction as their favored genre. These findings also signified that the students could gain many benefits from their preferences.